TERAS LANSIA: Interactive Education and Use of Herbal Drinks for Hypertension Management - Ayesha Uswatun Hasanah; Erni Ameliya; Rangga Aditya Pratama; Putri Wahiddatus Sa’diyah; Nurul Ma’rifa Ramadani; Zalfa Rania Muyassarah; Muhammad Sultan (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Hypertension is a common non-communicable disease among the elderly, but it often goes undetected early due to lack of knowledge and adherence to treatment. This community service program aims to improve the elderly's understanding and skills in self- managing hypertension through an educational and demonstrative approach. The activity was carried out at the Kenanga 2 Integrated Service Post (Posyandu), Loa Pari Village, involving 52 elderly participants. The implementation method included elderly exercise, blood pressure and BMI checks, a pre-test, interactive counseling on hypertension and drug myths, and a demonstration of making herbal drinks from local ingredients such as ginger, lemongrass, cinnamon, honey, and cucumber. Evaluation was carried out through a post-test and direct observation of participants' practice. The results showed an increase in participants' knowledge scores from a pre-test average of 79.22 to 93.45 in the post-test, with a paired t-test result of p = 0.011. This activity demonstrates that educational and practical interventions can improve elderly health literacy and serve as an additional strategy in sustainable hypertension control. Objective : This community service program aims to improve the elderly's understanding and skills in managing hypertension independently through an educational and demonstrative approach. Research Methods/ Implementation Methods : During the implementation phase, the elderly first took a pre-test in the form of true or false questions using interactive red and blue paper media. The pre-test was conducted in a structured manner and guided by a facilitator to make it easier for the elderly to understand. Then, a health check is carried out by health workers to determine the current health condition of the elderly, especially those who are at risk of hypertension. This stage also provided important information to the elderly about the need to monitor their blood pressure regularly. After the examination, a health education session on hypertension was held, with information delivered interactively by health experts using visual aids and language that was easy to understand. The counseling covers the definition of hypertension, normal and high blood pressure limits, the causes of hypertension, the dangers and symptoms of hypertension, as well as its treatment and management. In addition, the counseling also covers the types of hypertension medications and their effects and side effects, myths and facts about hypertension medications, the benefits of taking medication regularly, and strategies for establishing a medication routine. Furthermore, the elderly participated in a demonstration on making herbal drinks using natural ingredients such as ginger, lemongrass, cinnamon, and honey, as well as cucumber and honey. This demonstration was conducted with the aim of introducing healthy beverage options that can be consumed regularly by the elderly to help control blood pressure. From this activity, the elderly are expected to be able to imitate and apply it themselves at home.